Universal Design for Inclusion of People with Disabilities in Industrial Production Lines: structured analysis of publications (Estudos em Design, 2015)
Increasingly, organizations need to adapt their production lines to their audiences, including internal, allowing a wider range of people to have access to work. Thus, this article presents a comparative analysis of publications of universal design studies related to the inclusion of people with disabilities in industrial production lines. This work is guided by a framework of systematic literature review organized by filters, phases and stages in order to express the body of research about the search scope. As result, obtain the knowledge of the main gaps and opportunities in the area of publications. The conclusions of this article take relevance by promoting understanding of the processes of inclusion of people with disabilities in industrial production lines using universal design.
Keywords: Universal Design; People with Disabilities; Production Lines